Factibilidad económica de los programas de intervención ergonómica de los factores seguridad, carga y diseño físico en el área de Agroindustrias, ESPAM-MFL - Moreira Dueñas, Erika Lisseth (2015)
This research was based on a procedure for assessing the socio-economic impact of the ergonomics intervention programs, with the objective of studying the economic feasibility based on factors of security, load and physical design of the workplace in production units of the agro-industrial area. There was a check list of workers and coordinators to make an analysis of the current situation of the job identifying the risks, assessing the causes and consequences by the evaluation of several experts in relation to worker safety and health (OSH), using the method Kendall. This helped to identify the urgent of risk factors with the appropriate corrective action by proposing the plan for improvement of the investment in order to perform a financial analysis and compare the costs/benefits of the actions in worker safety and health. In the investment plan is analyzed the economic weight compared to the general budget of the institution where you could only invest up to 1% to meet the needs of the area. The result of the investment is economically feasible with the 0.06 %, demonstrating through the socialization of the socio-economic benefits that gets the worker in a comfortable environment, insurance, increasing the quality of life and motivation, representing to the company: sustainability, image, performance, decreasing turnover rates, employee absenteeism and low productivity, creating a safe work environment and health that values the most important part of the company the human talent.